Oceans'10 Ieee Sydney 2010
DOI: 10.1109/oceanssyd.2010.5603898
|View full text |Cite
|
Sign up to set email alerts
|

Model-based detection of radioactive contraband for harbor defense incorporating Compton scattering physics

Abstract: Abstract-The detection of radioactive contraband is a critical problem is maintaining national security for any country. Photon emissions from threat materials challenge both detection and measurement technologies especially when concealed by various types of shielding complicating the transport physics significantly. This problem becomes especially important when ships are intercepted by U.S. Coast Guard harbor patrols searching for contraband. The development of a sequential model-based processor that captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…4(d). The detection time and processing procedure we have described here in this single experiment is much too similar to the experimental measurement developed by the Candy research team [11][12][13]; however, we conjecture that the detection time is seldom an accurate representation of the performance of the processor because of the uncertainty inherent in nuclear radioactive physical procedures. It is therefore necessary to study the performance of this processor with repeated experiments.…”
Section: Singular Detection Experimentsmentioning
confidence: 84%
See 1 more Smart Citation
“…4(d). The detection time and processing procedure we have described here in this single experiment is much too similar to the experimental measurement developed by the Candy research team [11][12][13]; however, we conjecture that the detection time is seldom an accurate representation of the performance of the processor because of the uncertainty inherent in nuclear radioactive physical procedures. It is therefore necessary to study the performance of this processor with repeated experiments.…”
Section: Singular Detection Experimentsmentioning
confidence: 84%
“…In the proof-of-concept experiments, three radionuclides, cobalt ( 60 Co), cesium ( 137 Cs) and barium ( 133 Ba), were tested in the laboratory environment using the HPGe detector, and the experimental results indicated that the detection and identification of a radionuclide could be completed after collecting scores of counts of each monoenergetic source without requiring a pulse-height spectrum (PHS). Presently, a further research [13] presents that an extended processor incorporated with Compton scattering physics is more effective compared with the basic photoelectric only processor.…”
Section: Introductionmentioning
confidence: 99%
“…According to the proof-of-concept experiments using an HPGe detector and the radionuclides 60 Co, 137 Cs, and 133 Ba [5], the sequential Bayesian analysis approach exhibits promising detection ability, with a detection time sufficient for decision-making of no larger than a few seconds. An advanced processor coupled with both photoelectric effects physics and Compton scattering physics was later developed by Candy's research team, allowing more effective detection ability compared with the basic photoelectric-only processor [6]. However, to our knowledge, there is little in the literature concerning the performance of the sequential Bayesian detection system, or focusing on the development of this type of system, particularly regarding the key component of data acquisition.…”
Section: Introductionmentioning
confidence: 99%